The Advertising & Promotion an Integrated Marketing Communications Perspective Scientific Literature Review - Alemayehu Bakalo; Chalchissa Amantie (MultiTech Publisher, 2023)
The key objective of this study is to assess advertising and promotion from an IMC perspective. This study used a scientific literature review methodology with 50 existing articles completed in advert and promote and integrated marketing communications based on an inclusion/exclusion criterion. The findings of this study were collected by developing a thematic method, which involved extracting previous researchers' findings from the literature, classifying similar themes and findings, and drawing conclusions. According to the findings of this review, IMC means using multiple modes of communication, including advertising, personal selling, sales promotions, direct marketing, interactive marketing, publicity, and public relations. Finally, future researchers should IMC into the regeneration of concepts and the reconstruction of models and concepts to adapt to the new round of technological revolution and the changes carried about by user experience innovation. Bearing in mind the regular pattern of IMC concept change and comparing the evolution of IMC concepts and research topics in different periods.